Portuguese translation, cultural adaptation, and validation of the Person-Centered Practice Inventory - Care. - Diana Vareta; Célia Oliveira; Brendan McCormack; Paul Slater; Vaibhav Tyagi; Filipa Ventura (PLoS ONE)
Background In person-centered practice implementation and development, it is essential to incorporate standardized measurements that consider the perspectives of those involved in the therapeutic relationship. This work aims to translate, culturally adapt, and validate the Person-Centered Practice Inventory - Care (PCPI-C) for the Portuguese healthcare context. The PCPI-C is derived from the middle-range theory of the Person-Centered Practice Framework and is an 18-item self-reported inventory. Methods This methodological study followed a two-stage research design entailing the translation and cultural adaptation of the PCPI-C from English to European Portuguese and the Portuguese healthcare context in phase I, followed by a psychometric evaluation (N = 312) conducted using principal component and confirmatory factor analysis in SPSS version 27.0 and SPSS AMOS version 21.0 in phase II. The model was continuously and iteratively refined until it was considered acceptable per gold standard estimators. Results In phase I, the results revealed linguistic and contextual cultural differences compared to the original version. The cognitive debriefing showed that the respondents considered the items understandable and adequate for the purpose. In phase II, among the two adjusted PCPI-C models fit, i.e., first-order, and single-factor, the best fit to the empirical data was revealed by the single-factor structure, reflecting a good fit (x2/df = 2.408, CFI = .93, RMSEA = .07, SRMR = .05). Conclusions The PCPI-C is a valid and reliable instrument for assessing the perceptions of Portuguese service users regarding person-centered practice. It is necessary to consider the purpose for which the instrument is used to select the most appropriate measurement model, i.e., process evaluation as an outcome or as an inventory measure for continuous improvement.